Adaptive elastic net with distance correlation on the grouping effect and robust of high dimensional stock market price - Yusrina Andu,; Muhammad Hisyam Lee,; Algamal, Zakariya Yahya (Penerbit Universiti Kebangsaan Malaysia, 2021)
Stock market is found in many financial studies. Nonetheless, many of these literatures do not consider on the highly correlated stock market price. In particular, the studies on variable selection, grouping effects and robust dedicated to high dimension stock market price can be considered as scarce. Penalized linear regression using elastic net is one of the recognized methods to perform variable selection. However, the lack of consistency in variable selection may reduce the model performance. Hence, adaptive elastic net with distance correlation (AEDC) is proposed in this study and compared against elastic net, adaptive elastic net with elastic weight and adaptive elastic net with ridge weight. AEDC had lower mean squared error when the alpha increases from 0.05 to 0.95. Thus, the proposed method has successfully contributed to encouraging grouping effects between the highly correlated variables and also has an improved model performance in the presence of robustness.